Grado de competitividad de la ferretería arroba, franquicia “Disensa” en la parroquia La Unión del cantón Babahoyo en el año 2024. - Arias Dotan, Marnie Estrella (2025)
The Arroba Hardware Store Franchise “Disensa” is located in the La Unión Paris of the Babahoyo Canton in the year 2024, it is a company dedicated to the sale of hardware products, focusing on offering practical solutions for construction, remodeling and maintenance projects. However, despite being part of a recognized franchise, “Disensa” has faced a series of challenges, because local consumers prioritize price over product quality. This approach has hindered ist ability to attract and retain customers, especially in the face of local competitors that offer more affordable prices. The survey technique was used to analyze the perception in reference to products, services and prices to determine their position in the market, however, competitiveness in a Hardware Store is a key factor to attract and retain customers, in a market where consumers seek the best quality-price ratio, it is necessary to implement marketing strategies that boost its positioning in the market. These strategies should include promotions, discounts on popular or high-turnover products, and loyalty programs that reward customer loyalty, focusing on offering affordable prices to attract customers and increase sales without compromising the quality of products and services.